2017
DOI: 10.2147/cia.s143307
|View full text |Cite
|
Sign up to set email alerts
|

Application of Haralick texture features in brain [<sup>18</sup>F]-florbetapir positron emission tomography without reference region normalization

Abstract: ObjectivesSemi-quantitative image analysis methods in Alzheimer’s Disease (AD) require normalization of positron emission tomography (PET) images. However, recent studies have found variabilities associated with reference region selection of amyloid PET images. Haralick features (HFs) generated from the Gray Level Co-occurrence Matrix (GLCM) quantify spatial characteristics of amyloid PET radiotracer uptake without the need for intensity normalization. The objective of this study is to calculate several HFs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 19 publications
2
14
2
Order By: Relevance
“…Comparing the findings of the present study to those by Campbell et al [22], the authors reported results that state that energy and entropy best discriminate between the studied groups. While these features generally show statistically significant differences in our study, energy in the [ 18 F]FMM group is also one of the three HFs that are not significant when extracted from the global VOI.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Comparing the findings of the present study to those by Campbell et al [22], the authors reported results that state that energy and entropy best discriminate between the studied groups. While these features generally show statistically significant differences in our study, energy in the [ 18 F]FMM group is also one of the three HFs that are not significant when extracted from the global VOI.…”
Section: Discussionsupporting
confidence: 75%
“…Before GLCM computation, image intensities are quantized into 128 bins using equal probability quantization. A total of 6 HFs are calculated, namely energy, contrast, entropy, homogeneity, correlation, and dissimilarity [24,33], which have previously been used while analyzing amyloid PET images and have shown good performance [22,23]. On the other hand, the SUVRs are obtained by normalizing the average SUV of each region to the average SUV of the grey matter part of the cerebellum [8,14,34].…”
Section: Image Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Haralick texture features extracted from longitudinal 18F-florbetapir PET scans have been used to successfully differentiate between subject groups (eg, normal vs patients with mild cognitive impairment) without normalizing PET intensity using a reference region ( 16 ); it has been shown that first- and higher-order textual features with low-level variations are identified for reproducible solid tumor segmentation using FDG-PET/CT scans ( 17 ). In this study, we have, to the best of our knowledge, shown for the first time that a statistical model (CTI model) combining Haralick texture features computed from F-18 fluciclovine PET/CT images with patients’ clinical information may improve the chances of accurately detecting BCR.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Brynolfsson et al (2017) analyzed Haralick features extracted from apparent diffusion coefficient (ADC) MRI Images and assessed the sensitivity of these features against five image acquisition parameters. Similarly, Campbell et al (2017) also utilized Haralick features in a recent study for textural analysis of brain positron emission tomography (PET) images. In addition to being effectively used in medical textural analysis, Haralick features have also been effectively used in the quality control field ( Corbane et al, 2008 ; Bhandari and Deshpande, 2011 ).…”
Section: Related Workmentioning
confidence: 99%